ABOUT SOME MAIN SECURITY PROBLEMS AND PECULIARITIES OF TEACHING THE SUBJECT "AZERBAIJANI LANGUAGE" (EDUCATION IN THE 21ST CENTURY, 2025)
The aim of our research is to study and present the peculiarities of teaching the subject "Azerbaijani", some problems caused by the subject, as well as to propose some security issues that should be considered in the context of the examined topic. We give new approaches to the presented problems, questions worthy of attention, which imply a focused, consistent position, because the examined issues are not only a problem on a personal scale, but also on a national scale. It is narrow to consider the Azerbaijani language only in the framework of linguistics/linguistics, it should not be taken out of the state strategic framework, therefore we raise questions related to language-related security, socio-psychological, informational, national-cultural, economic, military and other issues.We have referred to the strategic positions required within the scope of the subject, unavoidable features, manifestations, desired approaches. The subject requires a broad, circumspect receptivity, starting from linguistics/linguistics, ending with ethno-linguistics, ethno-cultural, political science and other fields. The subject is self-explanatory. In order to ensure the purpose, problems, effectiveness, and educational outcomes of teaching the subject, the identity of the language and the audience (military educational institutions and universities) should be taken into account. As a result of the correct planning of teaching, the field of application of language knowledge is expanded.Our research was done on the basis of statistical data collection, summarization, results and observations recorded in the classrooms during the years of teaching in     military educational institutions, as well as following the dynamics of the field within the framework of activities in the educational environment for many years. The examined problems must always be within the framework of strategic steps not only of the sector, but also of the state. There should be a strict state control approach in this direction. By proposing the main problems, we present concluding provisions, a review of approaches to the subject. We suggest that within the framework of the examined topic, we also consider issues of language security, a safe environment for ensuring the knowledge of the Azerbaijani language, as well as the problems of effective assurance of results.Referring to the problems caused by the subject, the multifaceted problems arising from the subject, we present observations, approaches. The subject implies an important attitude, interdisciplinary importance, security issues, strict professionalism, involvement of trained specialists.
Keywords: аzerbaijani language; linguistic propaganda; linguistic safety; specialty language; military Azerbaijani; Azerbaijan; challenges of teaching; Azeriization of Armenian toponyms; Azerbaijani anti-Armenian and Armenophobic language propaganda.